Effects of different doses of dexmedetomidine on anaesthetic induction with alfaxalone – a clinical trial. (20th December 2013) - Pinelas, Rui; Alibhai, Hatim IK; Mathis, Alessandra; Jimenez Lozano, Angeles; Brodbelt, David C
Abstract Objective To document the effects of two doses of dexmedetomidine on the induction characteristics and dose requirements of alfaxalone. Study design Randomized controlled clinical trial. Animals Sixty one client owned dogs, status ASA I‐II. Methods Dogs were allocated randomly into three groups, receiving as pre‐anaesthetic medication, no dexmedetomidine (D0), 1 μg kg−1 dexmedetomidine (D1) intramuscularly (IM) or 3 μg kg−1 dexmedetomidine IM (D3). All dogs also received 0.2 mg kg−1 methadone IM. Level of sedation was assessed prior to induction of anaesthesia. Induction of general anaesthesia was performed with alfaxalone administered intravenously to effect at a rate of 1 mg kg−1 minute−1; the required dose to achieve tracheal intubation was recorded. Anaesthesia was maintained with isoflurane in oxygen. Cardiopulmonary parameters were recorded throughout the anaesthetic period. Quality of intubation, induction and recovery of anaesthesia were recorded. Quantitative data were compared with one‐way anova or Kruskal‐Wallis test. Repeated measures were log‐transformed and analysed with repeated measures anova (p < 0.05). Results Treatment groups were similar for categorical data, with exception of sedation level (p < 0.001). The doses (mean ± SD) of alfaxalone required for intubation were D0 1.68 ± 0.24, D1 1.60 ± 0.36 and D3 1.41 ± 0.43, the difference between D0 and D3 being statistically significant (p = 0.036). Heart and respiratory rates during the anaesthetic period were significantly different over time and between groups (p < 0.001); systolic arterial blood pressure was significantly different over time (p < 0.001) but not between groups (p = 0.833). Induction quality and recovery scores were similar between groups (p = 1.000 and p = 0.414, respectively). Conclusions and clinical relevance The administration of alfaxalone resulted in a good quality anaesthetic induction which was not affected by the dose of dexmedetomidine. Dexmedetomidine at 3 μg kg−1 IM combined with methadone provides good sedation and enables a reduction of alfaxalone requirements.